Investigation of somatic NKX2-5 mutations in congenital heart disease. Issue 2 (30th January 2009) - Draus, J M; Hauck, M A; Goetsch, M; Austin, E H; Tomita-Mitchell, A; Mitchell, M E
Abstract : Background: Reports of somatic mutations found in hearts with cardiac septal defects have suggested that these mutations are aetiologic in pathologic cardiac development. However, the hearts in these reports had been fixed in formalin for over 22 years. Because of the profound implication of this finding, we attempted to replicate it using fresh frozen tissue obtained in the current era from 28 patients with septal defects who underwent cardiac surgery and who were enrolled in our congenital heart disease tissue bank. Methods: Our cohort included patients with atrial septal defects (ASD, n = 13), ventricular septal defects (VSD, n = 5), and atrioventricular canal defects (AVCD, n = 10). Cardiac tissue samples were collected both from diseased tissue located immediately adjacent to the defect and from anatomically normal tissue located at a site remote from the defect (right atrial appendage). Tissue samples were immediately frozen in liquid nitrogen and stored at −80°C. Genomic DNA was isolated and amplified using the same methodology described in the previously published reports. 42 pathologic cardiac tissue samples were sequenced. Results: One non-synonymous germline sequence variant was identified in one patient. Two synonymous germline sequence variants were identified in two separate patients. A common single nucleotide polymorphism (SNP) was identified in 16 patients. Based on the incidence of somatic mutations described in the previously published reports, our study was adequately powered to replicate the previous studies. No evidence of somatic mutations was found in this study. Conclusion: Somatic mutations in NKX2-5 do not represent an important aetiologic pathway in pathologic cardiac development in patients with cardiac septal defects.